The effect of elevation and exposure on stability index and quantity of snags in pure Oriental beech (Fagus orientalis Lipsky.) managed forests - Özel, Halil Barış; Ayan, Sezgin; Varol, Tuğrul; Varol, Tuğrul; Özel, Halil Barış (My University, 2022)
Snags are a major structural and functional component in oriental beech (Fagus orientalis Lipsky.) because of their high degree of naturalness in northern Anatolia forests. This research, as a case study, was conducted in the even-aged and pure oriental beech managed forest in Bartın. In this research where the effect of exposure and elevation, zone factors on stability index, the number and volume of snags (standing coarse deadwood: CDWsnags) were examined. It was found that exposure did not affect the stability index, number and volume of CDWsnags. However, there is a significant difference among the elevation zone on the number of CDWsnags, their volume and stability index (P?0.000). It was found that there is an average volume of 8.87 m3 /ha of CDWsnags. The diameter of the snags is distributed between 32 and 72 cm. In addition, a strong positive correlation was determined between the number of CDWsnags and the stability index (r= 0.95), height and breast diameter of CDWsnags (r = 0.98). These results may be an important tool to be used to improve management interventions in the management of high value forests.
Keywords: Biyoloji; Çevre Bilimleri; Orman Mühendisliği; Oriental beech; Managed forest; stability index; standing deadwood; sustainable forestry